Dispersion of radionuclides from coal-fired brick kilns and concomitant impact on human health and the environment. (December 2020) - Abedin, M.J.; Karim, M.R.; Khandaker, Mayeen Uddin; Kamal, M.; Hossain, S.; Miah, M.H.A.; Bradley, D.A.; Faruque, M.R.I.; Sayyed, M.I.
Abstract: Realizing the probable health implications via the exposures to radionuclides released from coal-fired brick kilns, concentrations of terrestrial radionuclides in feed coal, fly- and bottom ash collected from some major coal-fired brick kilns of Southern region in Bangladesh were measured using HPGe γ-ray spectrometry. Respective mean activity concentrations (Bq kg −1 ) for 226 Ra, 232 Th and 4 0 K were found to be 36.3 ± 1.8, 26.2 ± 2.1 and 314 ± 18 in feed coal; 60.8 ± 3.9, 36.6 ± 3.9 and 338 ± 19 in fly ash; 54.9 ± 4.0, 39.7 ± 4.6 and 311 ± 18.0 in bottom ash samples. As a result of the combustion process, radionuclide concentration enhancements have been observed in proceeding from feed coal to fly- and bottom-ash. The calculated values of air absorbed dose-rates for fly- and bottom-ash are greater than the world average of 55 nGy/h reported by UNSCEAR, and the Lifetime Cancer Risk (LCR) approaches towards the safe limit recommended by the ICRP. As such, this does flag up a potential concern for those dwelling in nearby areas, especially for the coal workers who normally do not take any protective measures against exposure to ash dust. Multivariate statistical analysis has been used in examining for correlations between the origins of the radionuclides and their influence on the calculated radiological parameters. The measured data indicate significance for human health, also for the scientific community, and could be used for modeling studies in the region. Highlights: Coal fired brick kilns release terrestrial radionuclides via inhalable ash particles. Prolonged inhalation of smoke/ash gives rise enhanced radiation exposure to lungs. Hazardous level of absorbed dose and carcinogenic risk were found for exposed population Respiratory protection of kiln workers and members of public is highly recommended for radioprotection reasons. This study suggests the discharging management of fly ash should be revised significantly.